Facebook Features : Enhancing Student Engagement In Self-Regulated Learning - Zahidi, Zaihasriah (2010)
The purpose of this paper is to study the student engagement in self-regulated learning within a Facebook environment. An in depth study is conducted in terms of determining students\' motivation in utilizing Facebook to assist self-regulated learning, exploring student engagement evidence through the dimension of participation, interaction, social, cognitive and metacognitive in the students\' postings in performing self-regulated learning using Facebook, discovering the value of the contributed learning content to engage students in self-regulated learning within Facebook learning environment, identifying the students\' preferences of Facebook features that could encourage students to engage in self-regulated learning within Facebook learning environment and investigating the reasons of the preferences.